Alaska North Slope natural gas : hearing before the Committee on Energy and Natural Resources, United States Senate, One Hundred Sixth Congress, second session, to consider the transportation of Alaska North Slope natural gas to market and to investigate the cost, environmental impacts, and energy security implications to Alaska and the rest of the nation for alternative routes and projects, September 14, 2000. - United States. Congress. Senate. Committee on Energy and Natural Resources. (Washington : U.S. G.P.O. : For sale by the U.S. G.P.O., Supt. of Docs., Congressional Sales Office, 2001)
Shipping list no.: 2001-0143-P. Distributed to some depository libraries in microfiche. Microfiche. Microform. Mode of access: Internet.